2014
DOI: 10.1021/am503987j
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Porous Si Optical Biosensors: Effect of Thermal Oxidation on Their Performance and Properties

Abstract: The influence of thermal oxidation conditions on the performance of porous Si optical biosensors used for label-free and real-time monitoring of enzymatic activity is studied. We compare three oxidation temperatures (400, 600, and 800 °C) and their effect on the enzyme immobilization efficiency and the intrinsic stability of the resulting oxidized porous Si (PSiO2), Fabry-Pérot thin films. Importantly, we show that the thermal oxidation profoundly affects the biosensing performance in terms of greater optical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 55 publications
0
55
0
Order By: Relevance
“…ΔEOT/EOT 0 ), show a 2% increase in the relative EOT following APTES modification—indicating successful silanization of the PSiO 2 surface . Incorporation of CAA induces an additional increase in the relative EOT by ~3%, providing clear evidence that the PSiO 2 surface has been chemically modified …”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…ΔEOT/EOT 0 ), show a 2% increase in the relative EOT following APTES modification—indicating successful silanization of the PSiO 2 surface . Incorporation of CAA induces an additional increase in the relative EOT by ~3%, providing clear evidence that the PSiO 2 surface has been chemically modified …”
Section: Resultsmentioning
confidence: 91%
“…Before modification, a typical −(O y SiH x ) vibration mode was revealed at 801 cm −1 and a peak at 1039 cm −1 attributable to the SiOSi stretching mode. After modification with APTES, two additional peaks have emerged: one at 1636 cm −1 , ascribed to the bending of the primary amine, and the second at 1556 cm −1 , which is attributed to the bending of protonated amines . Following amidation with CAA, the spectrum shows a number of new bands around 1715, ascribed to carbonyl.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When He is used as the working gas without a substrate bias, a singular microstructure of closed pores oriented in the magnetron direction was obtained (see Figure 2a). In our previous works, we demonstrated that the pores are closed and incorporate a high amount of He (11,20), and we showed that the shadowing effects rule the growth mechanism responsible for the direction of the pores 13 and that changing the magnetron geometry was possible to orient the pores in a different direction 12 . The inset in Figure 2a shows in more detail the ellipsoidal shape and the size of the pores (lighter areas).…”
Section: Simulation Design and Characterization Of The Photonic Strumentioning
confidence: 78%
“…2 shows the FTIR spectra of PSf support and modified composite membranes. 36,37 Additionally, the peak of SO 3 2-is also detected at 1043 cm -1 . 8,33 The peak at 1541 cm -1 is assigned to the NH bending and torsional motion.…”
Section: Ftir and Xps Analysesmentioning
confidence: 91%